Complexity of postural sway affects affordance perception of reachability in virtual reality. Issue 12 (December 2020) - Masoner, Hannah; Hajnal, Alen; Clark, Joseph D; Dowell, Catherine; Surber, Tyler; Funkhouser, Ashley; Doyon, Jonathan; Legradi, Gabor; Samu, Krisztian; Wagman, Jeffrey B
Visual perception of whether an object is within reach while standing in different postures was investigated. Participants viewed a three-dimensional (3D) virtual reality (VR) environment with a stimulus object (red ball) placed at different egocentric distances. Participants reported whether the object was reachable while in a standard pose as well as in two separate active balance poses (yoga tree pose and toe-to-heel pose). Feedback on accuracy was not provided, and participants were not allowed to attempt to reach. Response time, affordance judgements (reachable and not reachable), and head movements were recorded on each trial. Consistent with recent research on perception of reaching ability, the perceived boundary occurred at approximately 120% of arm length, indicating overestimation of perceived reaching ability. Response times increased with distance, and were shortest for the most difficult pose—the yoga tree pose. Head movement amplitude increased with increases in balance demands. Unexpectedly, the coefficient of variation was comparable in the two active balance poses, and was more extreme in the standard control pose for the shortest and longest distances. More complex descriptors of postural sway (i.e., effort-to-compress) were predictive of perception while in the tree pose and the toe-to-heel pose, as compared with control stance. This demonstrates that standard measures of central tendency are not sufficient for describing multiscale interactions of postural dynamics in functional tasks.